FORMULASI SEDIAAN DEODORAN SPRAY EKSTRAKDAUN MANGKOKAN (Polyscias scutellaria (Burm.f.) Fosberg) DAN UJI EFEKTIVITAS ANTIBAKTERI Staphylococcus epidermidis - Huzaemah, Salma Haninah; Setiawan, Agus; Puspitasari, Ranny (Jurnal Riset Kefarmasian Indonesia, 2024)
The mangkokan plant (Polyscias scutellaria (Burm.f.) Fosberg) has properties as a diuretic, anti-inflammatory, breast inflammation, swelling and promotes milk production. Mangkokan leaves have antibacterial activity against bacteria that cause body odor. The purpose of this study was to determine the formulation and effectiveness of the antibacterial deodorant spray of mangkokan leaf extract (Polyscias scutellaria (Burm.f.) Fosberg) against Staphylococcus epidermidis bacteria ATCC 12228. The type of research used is in-vitro experimental. Mangkokan leaf extract is formulated in the form of a deodorant spray with a concentration of 10%, 15% and 20%. Preparation evaluation includes organoleptic, pH and viscosity tests. Antibacterial activity testing was carried out in-vitro using the disc diffusion method against S. epidermidis bacteria ATCC 12228. The results showed that the secondary metabolites contained in mangkokan leaves (Polyscias scutellaria (Burm.f.) Fosberg) were alkaloids, flavonoids, saponins, tannins and terpenoids. Mangkokan leaf extract spray deodorant preparation (Polyscias scutellaria (Burm.f.) Fosberg) can inhibit the growth of Staphylococcus epidermidis bacteria ATCC 12228 shown at a concentration of 20% with an average inhibition zone of 7.06 mm in the medium category. Preparation of deodorant spray for mangkokan leaf extract (Polyscias scutellaria (Burm.f.) Fosberg) with a concentration of 10%, 15% and 20% according to the requirements of SNI 16-4951-1998 namely organoleptic test, pH test, spray pattern, but does not meet the homogeneity requirements because there are extract granules. The results of data analysis using Kruskal Wallis obtained Asymp.Sig 0.015 (Sig. <0.05) which means that they reject H0 and accept H1. There was also a significant difference between F1 and the positive control.